2014
DOI: 10.3390/md12125856
|View full text |Cite
|
Sign up to set email alerts
|

Rumphellaoic Acid A, a Novel Sesquiterpenoid from the Formosan Gorgonian Coral Rumphella antipathies

Abstract: A novel sesquiterpenoid, rumphellaoic acid A (1), was isolated from the gorgonian coral Rumphella antipathies, and was found to possess a carbon skeleton that was obtained for the first time from a natural sources. The structure of 1 was elucidated by spectroscopic methods and this compound and was found to exert a moderate inhibitory effect on the release of elastase by human neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Organic extracts from the gorgonian belonging to the Rumphella genus in ecology and medical use, also were reported [7,8]. Our current studies on the constituents of R. antipathies led to the isolation of a novel ester derivative, rumphellolide J (1) ( Figure 1), derived by esterification of 4β,8β-epoxycaryophyllan-5-ol [9,10] and rumphellaoic acid A [11].…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Organic extracts from the gorgonian belonging to the Rumphella genus in ecology and medical use, also were reported [7,8]. Our current studies on the constituents of R. antipathies led to the isolation of a novel ester derivative, rumphellolide J (1) ( Figure 1), derived by esterification of 4β,8β-epoxycaryophyllan-5-ol [9,10] and rumphellaoic acid A [11].…”
mentioning
confidence: 67%
“…Furthermore, an HMBC correlation between H-5 ( H 4.58), an oxymethine proton, and the C-5 ester carbonyl carbon ( C 178.5) was found, which proved the existence of an ester linkage in 1. [11,12], and the results of a NOESY analysis (Figure 3). The atom configurations of the carbon skeleton (C-1,  C 42.5; C-8,  C 73.1; C-9,  C 36.2; and C-1,  C 49.0; C-4,  C 53.0; C-8,  C 41.7; C-9,  C 46.0) of 1 were found to be similar to those of 2 (C-1,  C 42.4; C-8,  C 72.7; C-9,  C 36.2) [9] and 3 (C-1,  C 48.9; C-4,  C 52.6; C-8, 41.9; C-9,  C 46.0) [11].…”
Section: -6 H 2 -7/c-4; H 2 -3 H 2 -6 H 2 -12/c-5; H 2 -6mentioning
confidence: 99%
See 1 more Smart Citation
“…695 The study also reported an extensive number of cometabolites 1080-1083 that had been previously reported from terrestrial plants or as semi-synthetic derivatives 1084-1090. Other sesquiterpenes 1091-1110 have been reported from Rumphella antipathies, [696][697][698] Lemnalia philippinensis, 699 Menella kanisa, 700 Nephthea erecta, 701 an unidentied gorgonian, 702 Dendronephthya sp., 703 Sinularia kavarattiensis, 704 Echinogorgia sassapo reticulata 705 and Anthrogorgia ochracea. 706 Of these sesquiterpenes, rumphellaoic acid A 1093 697 contains a unique skeleton, while shagenes A 1102 and B 1103 702 and ochracenoid A 1109 706 contain rarely reported skeletons.…”
Section: Cnidariansmentioning
confidence: 99%
“… 1 This sesquiterpenoid was isolated from Rumphella antipathies , a gorgonian coral that has produced several other caryophyllane and clovane sesquiterpenes ( Figure 1 ). 2 Isolation of 402 g of wet R. antipathies yielded only 0.9 mg of 1 . 1 Hushinone ( 2 ), birkenol ( 3 ), and birkenal ( 4 ) are noresesquiterpenoids identified in the essential oils obtained from the buds of Betula pubescens ssp.…”
mentioning
confidence: 99%